Clinical case of basal cell carcinoma therapy using 5 % imiquimod cream - H. I. Makurina; O. I. Мakarchuk; I. P. Dmytrenko; A. V. Holovkin; L. O. Cherneda (Zaporozhye State Medical University, 2020)
Aim. To describe clinical case of the basal cell carcinoma treatment, determine personalized diagnostic algorithm of the patient management with further selection of the therapy method regarding visual, dermatoscopic and pathomorphological picture of disease. Materials and methods. The own observation of clinical case of local treatment of the patient with basal cell carcinoma by means of 5% imiquimod cream was described. Results. Based on comprehensive examination of the patient with determination of features of visual, dermatoscopic and pathohistological picture the diagnosis "Basal cell carcinoma, nodular variant" was determined. Taking into account considerable traumatization and possibility of functional motor impairment after surgery it was determined to replace the treatment approach with the local use of 5 % imiquimod cream according to the standardized scheme. Step-by-step application of topical agent on the upper part of BCC affected area had also influence on the non-treated zone which began to regress by itself starting from the 9th week. Spontaneous regress of BCC stipulates rare and unusual course of disease. Control clinical and pathomorphological examination did not reveal any neoplastic processes in skin after 12 weeks course of treatment with 5 % imiquimod cream and within 1 year of further observation. In case of BCC the possibility of using topical agents increases therapeutic potential and compliance between doctor and patient. Conclusions. Annual increase of quantity of new cases of non-melanoma skin tumours and variability of clinical implications enable the rise of oncological suspicion level among practicing physicians. Creation of personalized algorithm of diagnostics ensures making the diagnosis timely and selection of differential treatment approach. Neglecting the neoplasm with significant affected area size the topical use of 5 % imiquimod is the effective alternative to invasive intervention for treatment of patients with the basal cell carcinoma.